How employers influence and can support the sustainability of employee families - Hine, Catherine (2019)
Employers face a ‘war for talent’; an increasingly competitive market for recruitment and retention of employees through which non-financial benefits organisational culture and reputation play an increased role. The Department for Work and Pension’s 2014 Family Test introduced a framework for policy makers to assess the potential impact of their practices on families of different structures and experiencing different family situations from family formation to transitions and separation. This qualitative research study used The Family Test framework to explore the accounts of employees working for different employers in the private and public sector and with diverse family structures and situations, to better understand how employers influence employee family situations and to learn which employer practices contribute to or undermine the sustainability of employee families.